Effect of Copper Sulfate On Hematological and Histological Parameters of Freshwater Fish Oreochromis niloticus at Various Sublethal Concentration : Life Sciences-Aquatic Toxicology - Sasikumar, S.; Leon, J. Prakash Sahaya (International Journal of Life Science and Pharma Research, 2022)
Heavy metals pollution is a great environmental problem in recent years throughout the world. Various activities such as domestic, anthropogenic activities, volcanic eruptions and industrial activities which increase their level of heavy metals concentration into the environment. Copper sulfate is used as an algaecide and fungicide in the fields of agriculture and aquaculture being discharged into water bodies and it can affect the aquatic organisms, especially fishes. The present study deals with the effect of copper sulfate on various hematological parameters of the experimental fish Oreochromis niloticus. Oreochromis niloticus is an important freshwater fish in commercial aquaculture. Fish is a significant food component of human food. Fish are the suitable bio-indicators of heavy metal contamination. Heavy metals are oxidative stress inducers in fish and can reflect aquatic contamination. The Objective of the present study was to analyze the hematological effects of heavy metal CuSO4 on the freshwater fish O.niloticus. The LC50 value of copper sulfate found to be 39.2 mg/L. The fish Oreochromis niloticus were experimented for the different sub lethal concentrations of 1/10, 1/20 and 1/30 of copper sulfate for the period of 30 days to get hematological changes. At the end of the experiment the result shows that the Red Blood Cell (RBC) count and the percentage of hemoglobin (Hb) were significantly decreased as the sub-lethal concentration of heavy metal Copper sulfate increased, while the level of WBC, MCV and MCH significantly increased. The effect of copper sulfate was observed by histopathological investigation of gill and liver of treated fish. The aim of present study is to investigate the hematological and histopathological effects of copper sulfate for the period of 30 days at various sublethal concentration in various tissues of the freshwater fish O. niloticus.Dietary data were collected in detail through face-to-face interview on tilapia O.niloticus consumption. Intake of fish (g) was computed. Statistical analyses were conducted using SPSS software for Windows and all tests were considered significant at p<0:05.